PENINDASAN DAN PERLAWANAN PEREMPUAN KULIT HITAM DALAM KARYA EVARISTO, GIRL, WOMAN, OTHER: SEBUAH STUDI FEMINIS - Zakiyatul Mufidah (Adabiyyāt: Jurnal Bahasa dan Sastra, 2024)
This study provides a reading of Evaristo’s Girl, Woman, Other in the light of Patricia Hill Collins’ framework of the Matrix of Domination to see how the novel generates Black women's discourse. This study aims to analyse the operation of the matrix of domination whereby the complex and interlocking oppression of Black women emerges in every domain of power. This study also attempts to reveal the forms of resistance as depicted throughout the storyline. A qualitative method was applied as the approach of this study, as the data are in the form of words and utterances. The writer collected the data by close-reading and coding the utterances and the narrator’s narration. The results of this study showed that the matrix of domination reappears in various forms of complex and interlocking oppression. Moreover, the study reveals the ways and strategies that Black women employ to resist entrenched interlocking oppression and reclaim cultural narratives through various means, including self-definition, educating Black daughters, and voicing Black aspirations and achievements.